Preparation of oriented poly(lactic acid) thin films by a combination of high temperature rubbing and thermal annealing: Impact of annealing parameters on structure, polymorphism and morphology. Issue 9 (24th January 2023) - Brosset, Marion; Herrmann, Laurent; Falher, Thierry; Brinkmann, Martin
Abstract: High temperature rubbing is a fast and low‐cost method to prepare highly oriented films of polymers. This contribution describes the fabrication of smooth and pin‐hole‐free poly(lactic acid) (PLA) thin films of controlled structure and morphology using a combination of rubbing at moderate temperature (T ≤ 100°C) and thermal annealing. We investigate the impact of annealing temperature and duration on the structure of rubbed PLLA and stereo‐complex (SC) thin films. The importance of annealing parameters on polymorphism, crystallinity, crystal dimensions and in‐plane orientation are analyzed using Transmission Electron Microscopy, Differential Scanning Calorimetry and FTIR spectroscopy. Regarding SC PLA films, the conditions are identified to fully transform the equimolar PLLA‐PDLA blend films into pure oriented SC films without presence of homocrystals. Abstract :